A Cross-Linguistic Investigation of Affricates - Liker, Marko; Alan, Wrench; Gibbon, Fiona (2005)
The aim was to use electropalatography (EPG) to investigate the closure phase of affricate /  / and compare it with the closure phase of stop / / in four languages (English (N=2), Catalan (N=2), Italian (N=2) and Croatian (N=1)) in different vowel contexts. ACoG measured at 10 equally spaced sample points of normalized closure phases of affricates in different vowel contexts shows that the place of articulation of affricates either remains the same or becomes slightly more posterior at the end of the closure phase in all languages. The same index shows that the place of articulation of stops either remains unchanged throughout the closure or becomes more anterior in all languages. It is also clear that the manner of movement of the place of articulation differs in affricates as opposed to stops in all languages. Average ACoG at maximum contact point in different vowel contexts shows that stops are more anterior than their affricate counterparts in all languages, but the degree of that difference is different in the four languages. The difference in the duration of the closure shows that in all languages except in English affricates have shorter duration of their closure phases than their stop counterparts.
Projekt MZOS
ENG